[PP.10.03] SUCCESSFUL RENAL DENERVATION FOR RESISTANT HYPERTENSION FAILS TO IMPROVE INSULIN RESISTANCE AS ASSESSED BY HYPERINSULINEMIC EUGLYCEMIC STEP-CLAMP AND GLUCOSE TRACER INFUSION. (September 2016) - Miroslawska, A.; Gjessing, P.; Solbu, M.; Fuskevåg, O.; Jenssen, T.; Steigen, T.
Abstract : Objective: The purpose of this study was to determine whether insulin sensitivity is improved after successful renal denervation (RDN) treatment for resistant hypertension. Design and method: Non-randomized, prospective study of 23 non-diabetic patients with resistant hypertension undergoing a two-step hyperinsulinemic euglycemic clamp with glucose tracer and labeled glucose infusion (HEC) as well as an oral glucose tolerance test (OGTT) before and 6 months after RDN. Whole body glucose disposal (WGD) and endoogenous glucose release (EGR) were calculated. Results: Eighteen of the 23 patients had metabolic syndrome at baseline, and body mass index (32 ± 5 kg/m2 at baseline) was stable during the study. At baseline, fasting plasma glucose was 5.9 ± 0.7 mmol/L, plasma insulin was 147 ± 93 pmol/L and plasma c-peptide was 1456 ± 502 pmol/L. No significant changes in these parameters were observed after 6 months. Basal glu-cose turnover rate and glucose infusion rate during two-step clamping remained unchanged. Suppression of endogenous glucose release during low-dose insulin infusion decreased from 0.9 ± 0.4 to 0.8 ± 0.4 mg/kg/min (p = 0.02), but remained unchanged during high insulin infu-sion. Area under the curve 0–120 min for glucose and insulin during OGTT, homeostasis model assessment-insulin resistance (HOMA-IR), Quantitative Insulin Sensitivity Check Index (ISQUICKI), the Simple Index assessing Insulin Sensitivity oral glucose tolerance (SIisOGTT) did not change significantly. Whole body glucose disposal did not change from basal levels at follow-up (Figure 1). Figure. No caption available. Conclusions: Despite a significant effect on blood pressure, RDN treatment did not improve peripheral or hepatic insulin sensitivity, in this group of non-diabetic patients with resistant hypertension, as assessed by two-step HEC with glucose tracer infusion as well as indices derived from OGTT and fasting blood samples 6 months after RDN.